2000
DOI: 10.1159/000007004
|View full text |Cite
|
Sign up to set email alerts
|

Dependency of Premature Ventricular Contractions on Heart Rate and Circadian Rhythms during Childhood

Abstract: The aim of the present study was to identify and quantify the rate dependence of premature ventricular contractions (PVC) during childhood. A 24-hour Holter recording was performed in 16 consecutive children, aged 22 days to 11 years (mean age 5.6 years), with frequent (>5,000/day), isolated monomorphic PVC. Those PVC were identified and the length of the preceding sinus cycle was measured. The values were ordered into 50-ms class intervals, and the percentage of PVC for each class was calculated and then anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Differences between recordings of ambulatory and hospitalized children are unlikely because rhythmic events occur mainly during sleep, such as minimal heart rate, marked sinus arrhythmia or conduction disorders. On the other hand, differences may be observed in the heart rate distribution, which depends on the physical activity, and also in the incidence of arrhythmias, which depends on the autonomic balance, physical activity, emotional stress, circadian rhythms or heart rate itself [10]. The pathophysiological mechanisms underlying the genesis of arrhythmia remain substantially unknown.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Differences between recordings of ambulatory and hospitalized children are unlikely because rhythmic events occur mainly during sleep, such as minimal heart rate, marked sinus arrhythmia or conduction disorders. On the other hand, differences may be observed in the heart rate distribution, which depends on the physical activity, and also in the incidence of arrhythmias, which depends on the autonomic balance, physical activity, emotional stress, circadian rhythms or heart rate itself [10]. The pathophysiological mechanisms underlying the genesis of arrhythmia remain substantially unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The pathophysiological mechanisms underlying the genesis of arrhythmia remain substantially unknown. The dependency of ventricular arrhythmia on circadian rhythms during childhood has been demonstrated [10]. Moreover, it is possible to identify a spontaneous trend between their incidence and the length of the preceding cardiac cycle [10].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In older children and young adults, the incidence increases, although exact numbers are unknown since most patients are asymptomatic ( 14 ). Pediatric PVCs exhibit variability in terms of frequency, complexity, and configuration, which can change over time and may be influenced by factors such as age, autonomic tone, and myocardial substrate ( 15 ). Holter monitoring studies have demonstrated a higher prevalence, detecting PVCs in up to 41% of children over a 24-hour period, suggesting that intermittent PVCs may be a common and transient occurrence in this demographic ( 16 ).…”
Section: Epidemiologymentioning
confidence: 99%